The role and clinical implications of HIF-PHI daprodustat in dialysis-dependent and non-dialysis-dependent chronic kidney disease anemic patients: a general review - Waheed, Yousuf Abdulkarim; Liu, Jie; Almayahe, Shifaa; Sun, Dong (Frontiers in Nephrology, 2024)
Chronic kidney disease (CKD) patients often suffer from complications such as anemia as the kidney function declines. More than 25% of CKD hemodialysis patients in China are complicated with renal anemia due to renal and hepatic impairment in the production of erythropoietin (EPO). In recent years, prolyl hydroxylase domain (PHD) inhibitors have been approved in China and Japan for the treatment of CKD patients complicated with anemia. Daprodustat is a novel orally administrated active hypoxia-induced factor-prolyl hydroxylase inhibitor (HIF-PHI) that may improve quality of life and ischemic conditions such as peripheral arterial disease (PAD), stimulate the synthesis of endogenous EPO, and can effectively induce the production of red blood cells. It has been shown to increase EPO levels, which can lead to an increase in hemoglobin (Hgb), hematocrit, and red blood cell counts. Clinical studies have shown its effectiveness in dialysis and non-dialysis CKD anemic patients. In this literature review, we will focus on the mechanism and metabolism of the drug as well as its clinical applications in dialysis and non-dialysis CKD patients and summarize the adverse reactions.